Power Supplies for Arctic Radio Repeater Systems - Nagy,Gerald D (1978)
This feasibility study assesses various long-lived, self-contained 30-watt power supplies for an Arctic Radio Repeater System. The study involves a review of the state-of-the-art, availability and cost of five candidate systems; batteries, fuel cells, radioisotopic thermoelectric generators, fueled thermoelectric generators and windmill-battery systems. The above five candidates were also assessed as standby power units. Reliability, service and maintenance requirements are considered since the application calls for one year unattended operation and servicing by light helicopter on a single annual flight for all sites. Only zinc/air batteries with lead/acid batteries for the standby system are available now. Their cost is moderate, but zinc/air cells are heavy and must be replaced each year. Other systems could be available in the 1980's but they would require various amounts of development work and evaluation in an arctic environment. Recommendations and priorities for development of the systems which could replace the zinc/air cells at a later date are given. (Author)